MACROALGAE DIVERSITY IN CORAL REEFS AT THE WATERS OF TELUK TAMIANG VILLAGE, KOTABARU - Muhammad Ahsin Rifa’i; Muhammad Syahdan; Hadiratul Kudsiah (TROPICAL WETLAND JOURNAL, 2016)
The purpose of this study was to map the distribution of macroalgae at the waters of Teluk Tamiang Village, Kotabaru, South Kalimantan. The results showed that there were 8 species of macroalgae living in coral reef ecosystems. They originated from 7 order, 8 family, 8 genera, consisting of Acanthopora muscoides, Gracilaria coronopifolia, Amphiroa fragillissima Chlorodesmis sp., Halimeda macroloba, Enteromorpha sp., Turbinaria conoides, and Dictyota pinnatifida. The diversity index of two stations observed in this study was low.